2022
DOI: 10.3389/fsurg.2022.855695
|View full text |Cite
|
Sign up to set email alerts
|

Liver Graft-to-Spleen Volume Ratio as a Useful Predictive Factor of the Outcomes in Living Donor Liver Transplantation: A Retrospective Study

Abstract: BackgroundIn living donor liver transplantation (LDLT), graft-to-recipient weight ratio (GRWR) <0. 8% is an important index for predicted portal hypertension, which may induce the graft small-for-size syndrome (SFSS). Recently, the value of graft-to-spleen volume ratio (GSVR) on predicted portal hypertension had been reported, whether without splenectomy prevent portal hypertension in transplantation remains disputed, we aimed to identify GSVR contributing to portal venous pressure (PVP) and outcomes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…There is some evidence that graft-to-spleen-volume-ratio (GSVR) may guide decision on the need for PIM. [145][146][147][148][149] Gyoten et al reported that GSVR <0.95 predicts PVP of >20 mm Hg. 150 Cheng et al reported a GSVR of <0.60 was highly associated with post-transplant elevated PVF.…”
Section: Indications For Pim In Sfsgmentioning
confidence: 99%
“…There is some evidence that graft-to-spleen-volume-ratio (GSVR) may guide decision on the need for PIM. [145][146][147][148][149] Gyoten et al reported that GSVR <0.95 predicts PVP of >20 mm Hg. 150 Cheng et al reported a GSVR of <0.60 was highly associated with post-transplant elevated PVF.…”
Section: Indications For Pim In Sfsgmentioning
confidence: 99%